Modified Huang-Lian-Jie-Du Decoction Ameliorates Aβ Synaptotoxicity in a Murine Model of Alzheimer's Disease. (3rd November 2019) - Liu, Yan; Du, Ting; Zhang, Wenlong; Lu, Weiye; Peng, Zhichao; Huang, Shuqiong; Sun, Xiangdong; Zhu, Xiaoqin; Chen, Chaojun; Qian, Linchao; Wen, Lei; Xu, Pingyi; et al.
Abstract : Alzheimer's disease (AD) is a common neurodegenerative disease, characterized by cognitive dysfunction; however, the therapeutic strategies are not fully understood. Huang-Lian-Jie-Du-Decoction (HLJDD) is a famous traditional Chinese herbal formula that has been widely used clinically to treat dementia. Recently, according to previous study and our clinical practice, we generate a new modification of HLJDD (named modified-HLJDD). In this study, we indicated that modified-HLJDD attenuated learning and memory deficiencies in A β 1-42 oligomer-induced AD model, and we confirmed the exact metabolites in modified-HLJDD solution, as compared with HLJDD by UHPLC-Q-TOF-MS. Using GC-Q-TOF/MS-based metabolomics, we identified adenosine as the potential significant metabolite, responsible for modified-HLJDD regulating energy metabolism and synaptic plasticity in AD model. We also revealed that the potential underlying mechanism of modified-HLJDD in AD model may involve NMDA receptor-mediated glutamatergic transmission and adenosine/ATPase/AMPK cascade. Moreover, we also indicated the differential gut microbiota which mainly involved Firmicutes, Bacteroidetes, Proteobacteria, and Actinobacteria at the phylum level upon modified-HLJDD treatment in AD model. Based on the correlation of metabolomic analysis with microbiome analysis, we clarified that Dorea is the most affected microbiota with adenosine upon modified-HLJDD treatment in AD model. Thus, our study suggests that modified-HLJDD may serve as a potential therapeutic drug in treating AD.